PENDAURAN LAHAN TEMPAT PEMBUANGAN AKHIR (TPA) DENGAN PERBAIKAN TANAH SECARA MEKANIS - Indra Bhaswara Purnomosidy; Aniek Prihatiningsih (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2021)
In recent decades Indonesia has experienced a massive population boom, as such adequate facilities are needed. One thing that can be done is the usage of land for landfills to become the providing land for said infrastructure. This study uses the library research method for its processing or it is also called library research for data comparison. The data sources used are primary and secondary data derived from Google Scholar. The data will be analyzed using descriptive analysis method. The theoretical basis used is the theory of soil improvement methods and the handling of leachate as well as methane gas. The final result of the research is a results comparison of settlement and the bearing capacity of the soil that has undergone improvement and the soil that has not undergone improvement. From the research it can be concluded that the suitable method for landfill improvement is Stone Column. Pertumbuhan penduduk di Indonesia dalam beberapa dekade terakhir meningkat sehingga dibutuhkan fasilitas yang memadai, salah satunya dengan memakaian lahan Tempat Pembuangan Akhir (TPA) menjadi sarana infrastruktur. Penelitian ini menggunakan metode library research yang disebut juga penelitian kepustakaan dengan membandingkan data. Adapun sumber data yang digunakan adalah data-data primer dan sekunder dari Google Scholar. Data akan dianalisa dengan metode deskriptif analisis. Landasan teori digunakan adalah teori Metode Perbaikan Tanah dan penanganan Lindi serta Gas Metana. Hasil akhir dari penelitian adalah perbandingan hasil penurunan dan daya dukung tanah sebelum perbaikan dan setelah perbaikan. Hasil penelitian menunjukkan bahwa metode yang cocok untuk pebaikan tanah TPA mengunakan Stone Column.